The moderation of maternal parenting on the association of trauma, dissociation, and psychosis in depressive inpatients. Issue 1 (31st December 2022) - Li, Dian-Jeng; Hsieh, Yung-Chi; Chiu, Chui-de; Lin, Ching-Hua; Chou, Li-Shiu
ABSTRACT: Background: The effect of dissociation and parenting style on the relationship between psychological trauma and psychotic symptoms has not previously been investigated. Objective: The aim of this study was to develop a moderated mediation model to assess whether the association between psychological trauma and psychotic symptoms is mediated by dissociation and moderated by parental maltreatment. Methods: Inpatients with major depressive disorder (MDD) and bipolar depression (BP) were recruited. Self-reported and clinical rating scales were used to measure the level of dissociation, psychotic symptoms, history of psychological trauma and parental maltreatment. The PROCESS macro in SPSS was used to estimate path coefficients and adequacy of the moderated mediation model. High betrayal trauma (HBT), low betrayal trauma (LBT), paternal maltreatment, and maternal maltreatment were alternatively entered into the conceptual model to test the adequacy. Results: A total of 91 patients (59 with MDD and 32 with BP) were recruited, with a mean age of 40.59 ± 7.5 years. After testing with different variables, the moderated mediation model showed that the association between LBT and psychotic symptoms was mediated by dissociation and moderated by maternal maltreatment. A higher level of maternal maltreatment enhanced the effect of LBT on dissociation. Conclusions: Healthcare workers should be aware of the risk of developing psychotic symptoms among depressive patients with a history of LBT and maternal maltreatment. HIGHLIGHTS: We explored associations between trauma, dissociation, and psychotic symptoms. Low betrayal trauma (LBT) fit the conceptual model. Dissociation mediated the association between LBT and psychotic symptoms. Maternal maltreatment exacerbated the effect of LBT on dissociation.